CITIZEN PARTICIPATION IN TRADITIONAL ALGERIAN SOCIETIES: THE CASES OF NEW KSOUR OF MZAB AND THE VILLAGE OF AIT EL KAID - Timhadjelt Sabiha; Gueliane Nora (International Journal of Innovative Technologies in Social Science, 2024)
The concept of citizen participation emerged towards the end of the twentieth century as part of the new democratic paradigms of the Western countries of America and Europe. However, citizen participation is an ancient principle that has guided the political, economic and social management systems of many ancient indigenous social groups. The aim of this paper is to examine the concept of citizen participation and the mechanisms implemented in the management of the environment and daily life in traditional Algerian societies, through the study of two cases: the experience of the new ksour in the M’Zab in Ghardaïa, and the project to classify the village of Ait El Kaid as a protected sector in Tizi Ouzou. The results of this study reveal the particularities of the participatory processes in each case, such as tajmaat in the Kabyle villages and twiza in the process of building the new ksour, while highlighting the similarities and differences specific to each.